Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 9 - Section 9.3 - Solving Pairs of Linear Equations by Substitution - Exercises - Page 334: 9



Work Step by Step

$x-6y=3$ $3y=x$ Substitute 3y for x in the first equation. $3y-6y=3$ $\longrightarrow$ simplify $-3y=3$ $\longrightarrow$ divide both sides by -3 $-3y\div-3=3\div-3$ $\longrightarrow$ simplify $y=-1$ Substitute -1 for y in the second equation. $3(-1)=x$ $\longrightarrow$ simplify $-3=x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.